2015
DOI: 10.1097/mnh.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Dialysate content and risk of sudden cardiac death

Abstract: Dialysate content plays an important role in the risk of SCD in hemodialysis patients on hemodialysis. There is a need for further studies designed to identify patients at risk and to determine what strategies can be used to lower this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
(34 reference statements)
0
18
0
1
Order By: Relevance
“…6,1418 The potential hazards of very low (< 2 mEq/L) DK are triggered by a larger removal of potassium during HD causing intradialytic and post-dialysis hypokalemia, and often a rapid rebound of potassium levels post-dialysis, contributing to cardiac instability. 30 In our primary analysis comparing more common DK prescriptions, we found a similar risk of adverse events; any differences were modest and unlikely to be clinically important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,1418 The potential hazards of very low (< 2 mEq/L) DK are triggered by a larger removal of potassium during HD causing intradialytic and post-dialysis hypokalemia, and often a rapid rebound of potassium levels post-dialysis, contributing to cardiac instability. 30 In our primary analysis comparing more common DK prescriptions, we found a similar risk of adverse events; any differences were modest and unlikely to be clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 While no recommendation on DK levels has been provided in the Kidney Disease Outcomes Quality Initiative (KDOQI) cardiovascular disease guidelines, 13 several recent reviews are in agreement that DK < 2 mEq/L should be avoided, particularly in patients with high pre-dialysis potassium, to avoid a rapid decrease in plasma potassium. 6,1418 Accordingly, anecdotal reports indicate that the use of DK < 2 mEq/L has become increasingly rare. This prompted us to investigate whether DK = 2 mEq/L was still too low, in comparison to a higher DK of 3 mEq/L.…”
Section: Introductionmentioning
confidence: 99%
“…Dialysate composition may play an important role in all-cause mortality and sudden cardiac death as well [18][19][20]. Several studies have shown that a lower D-Ca may increase the chance of sudden cardiac death, whereas a higher D-Ca may cause positive Ca balance leading to vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…HD treatment aims to correct metabolic acidosis via bicarbonate concentration of the dialysate [ 123 ], ultrafiltration rate [ 124 ], dialyzer membrane surface area and permeability [ 125 ], blood and dialysis flow rate [ 124 ], transmembrane concentration gradient set by the patient’s serum bicarbonate level and bicarbonate availability from the dialysate [ 125 ], and dialysis adequacy [ 122 , 123 ] through maintaining the pre-dialysis serum bicarbonate levels between 24 and 26 mmol/L as recommended by current opinion [ 126 ]. However, metabolic acidosis correction depends on patient-related determinants such as interdialytic weight gain [ 123 ], acid generation from high protein intake [ 122 , 127 ], or gastrointestinal losses of bicarbonate [ 122 , 125 ]. Individual fluctuation in patients’ bicarbonate levels challenges optimum management [ 122 ].…”
Section: Iatrogenic Factors Of Malnutritionmentioning
confidence: 99%